In silico characterization of blaNDM-harboring plasmids in Klebsiella pneumoniae - Zeng, Zhu; Lei, Lei; Li, Linman; Hua, Shengni; Li, Wenting; Zhang, Limei; Lin, Qiuping; Zheng, Zhixiong; Yang, Jing; Dou, Xiaohui; Li, Luan; Li, Xiaobin (Frontiers in Microbiology, 2022)
Klebsiella pneumoniae is a primary culprit of antibiotic-resistant nosocomial infections worldwide, and infections caused by NDM-producing strains are a major threat due to limited therapeutic options. The majority of blaNDM cases occur on plasmids; therefore, we explored the relationships between plasmids and blaNDM genes in K. pneumoniae by analyzing the variants of blaNDM, replicon types, conjugative transfer regions of 171 blaNDM-harboring plasmids from 4451 K. pneumoniae plasmids. Of the nine identified blaNDM variants, blaNDM-1 (73.68%) and blaNDM-5 (16.37%) were the most dominant. Over half of the blaNDM-harboring plasmids of K. pneumoniae were classified into IncF plasmids. IncX3 single-replicon plasmids (46–57 kb) carried genes encoding relaxases of the MOBP family, T4CP genes of the VirD4/TraG subfamily, and VirB-like T4SS gene clusters, which were mainly geographically distributed in China. We found ten blaNDM-harboring IncN plasmids (38.38–63.05 kb) carrying the NW-type origin of transfer (oriT) regions, genes coding for relaxases of MOBF family, genes encoding T4CPs of the TrwB/TraD subfamily, and Trw-like T4SS gene clusters, which were also mainly geographically distributed in China. Moreover, we identified 21 IncC plasmids carrying blaNDM-1 (140.1–329.2 kb), containing the A/C-type oriTs, genes encoding relaxases of MOBH family, genes encoding T4CPs belonging to TrwB/TraD subfamily, and Tra_F-like T4SS gene clusters. The blaNDM-harboring IncC plasmids were widely geographically distributed all over the world, mainly in the USA, China and Viet Nam. These findings enhance our understanding of the diversity of blaNDM-harboring plasmids in K. pneumoniae.